What Is Expected from a Facial Trauma Caused by Violence? - Douglas Rangel Goulart; Lucas do Amaral Colombo; Márcio de Moraes; Luciana Asprino (Stilus Optimus, 2014)
Objectives: The aim of this retrospective study was to compare the peculiarities of maxillofacial injuries caused by interpersonal violence with other etiologic factors. Material and Methods: Medical records of 3,724 patients with maxillofacial injuries in São Paulo state (Brazil) were retrospectively analyzed. The data were submitted to statistical analysis (simple descriptive statistics and Chi-squared test) using SPSS 18.0 software. Results: Data of 612 patients with facial injuries caused by violence were analyzed. The majority of the patients were male (81%; n = 496), with a mean age of 31.28 years (standard deviation of 13.33 years). These patients were more affected by mandibular and nose fractures, when compared with all other patients (P < 0.01), although fewer injuries were recorded in other body parts (χ2 = 17.54; P < 0.01); Victims of interpersonal violence exhibited more injuries when the neurocranium was analyzed in isolation (χ2 = 6.85; P < 0.01). Conclusions: Facial trauma due to interpersonal violence seem to be related to a higher rate of facial fractures and lacerations when compared to all patients with facial injuries. Prominent areas of the face and neurocranium were more affected by injuries.